Why We Don’t Need a MERS Vaccine - Pranav Aurora (Voices in Bioethics, 2015)
On the heels of the Ebola outbreak, the globe is confronting another potential pandemic – the Middle Eastern respiratory syndrome (MERS) virus. With reported cases now reaching at least 26 countries[i] and the death total climbing towards 500,[ii] MERS has surfaced to international attention since its initial outbreak in Saudi Arabia in 2012. In particular, the global scale of this infectious disease has moved the scientific community to antagonize big pharmaceutical companies for not developing a vaccine.[iii]